Study on the effects of online classes, product of the pandemic produced by covid-19 - Linares, Oscar (2020)
ABSTRACT The present work is a systematic review article, better known as an analysis of the state of the art, the work is focused on being able to analyze the different factors that have occurred in the change of the different ways of studying towards the online modality, the The year 2020 was the year of the adaptation of all modalities, all levels, regardless of the social, economic, geographical location, among others, product of the pandemic produced by COVID-19, a temporary study of publications was carried out related to the changes that have occurred in all the actors of the world educational system, presented a summary table with the important data in each of the studies, as well as a description of the study, in total 10 scientific articles published in different journals were taken all of them indexed in SCOPUS and in most of the continents, presenting at the end a conclusion regarding the analyzed jobs and positions at your service.